PROTEIN-LIGAND BINDING DATA INTEGRATION FOR "DIABETES DISEASE RELATED STUDIES" IN DIFFERENT ORGANISM - D.PONMARY PUSHPA LATHA; D.JEYA SUNDARA SHARMILA (International Journal of Pharma and Bio Sciences, 2013)
Protein-Ligand Binding Data of Diabetes Disease Related Studies is fashioned to provide the amino acid compositions of the following organisms in the ligand binding environment: Escherichia coli, Homo sapiens, Mus musculus, Oryctolagus cuniculus, Rattus norvegicus, Sus scrofa, Saccharomyces cerevisiae and Spodoptera frugiperda. The physico-chemical properties and quantum mechanical descriptors of the diabetes disease related ligands are depicted. Keyword search for the chemical name and related information are incorporated in the database. The average tightness and co-crystal contact of ligand binding in different organisms are also calculated. Atomic coordinates for ligands are annexed in XML format. http://www.ponmary.com/LandingPage/dia/Diamain.html)